2017
DOI: 10.1021/acs.jpcc.7b04348
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature CO Oxidation over Combustion Made Fe- and Cr-Doped Co3O4 Catalysts: Role of Dopant’s Nature toward Achieving Superior Catalytic Activity and Stability

Abstract: Co3O4 with a spinel structure shows unique activity for CO oxidation at low temperature under dry conditions; however the active surface is not very stable. In this study, two series of Fe- and Cr-doped Co3O4 catalysts were prepared by a single-step solution combustion technique. Fe was chosen because of its redox activity corresponding to the Fe2+/Fe3+ redox couple and compared to Cr, which is mainly stable in the Cr3+ state. The catalytic activity of new materials for low-temperature CO oxidation was correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 49 publications
5
42
0
Order By: Relevance
“…The HR-TEM image of the FeV-a/meso-Co hybrid (Figures 3C-E) showed smaller particles than its corresponding meso-Co, credited to Fe, and V coordinated with Co-cations in decreasing Co 3 O 4 particle size. 65 Figure 3F displays the lattice distance in the HR-TEM photographs agrees with the (311) interplanar distance of the Co 3 O 4 , further proving that the assynthesized FeV-a/meso-Co 3 O 4 sample is well crystallized.…”
Section: Morphological Features Of Fev/ Meso-cosupporting
confidence: 58%
“…The HR-TEM image of the FeV-a/meso-Co hybrid (Figures 3C-E) showed smaller particles than its corresponding meso-Co, credited to Fe, and V coordinated with Co-cations in decreasing Co 3 O 4 particle size. 65 Figure 3F displays the lattice distance in the HR-TEM photographs agrees with the (311) interplanar distance of the Co 3 O 4 , further proving that the assynthesized FeV-a/meso-Co 3 O 4 sample is well crystallized.…”
Section: Morphological Features Of Fev/ Meso-cosupporting
confidence: 58%
“…The two main peaks at 778.77 eV and 794.06 eV correspond to Co-2p 3/2 and Co 2p 1/2 . The binding energy separation between Co-2p 1/2 and Co-2p 3/2 was found to be 15.29 eV, which is in good agreement with reported values 30 . The main and shake up peaks appeared at high binding energies of 778.77 eV and 782.15 eV respectively is attributed to the presence of Co 2+ which affirmed with reported values 11,17 .…”
Section: Resultssupporting
confidence: 91%
“…Figure 5 shows the high resolution XPS core level spectra of Co-2p and S-2p. The spin-orbital splitting of Co-2p peaks are deconvoluted into two main peaks, two low intense peaks with associated satellite peaks 30 (Fig. 5a).…”
Section: Resultsmentioning
confidence: 99%
“…The doping of In 2 O 3 induced the structural distortion of Co 3 O 4 and promoted the catalytic performance of Co 3 O 4 for CO oxidation [13]. Baidya et al demonstrated that 15% Fe-doped Co 3 O 4 can achieve superior catalytic activity and stability towards CO oxidation [14].…”
Section: Introductionmentioning
confidence: 99%